Feature Fatigue: When Product Capabilities Become Too Much of a Good Thing - Thompson, Debora Viana; Hamilton, Rebecca W.; Rust, Roland T. (Journal of Marketing Research, 2005)
As technology advances, it becomes more feasible to load products with a large number of features, each of which individually might be perceived as useful. However, too many features can make a product overwhelming for consumers and difficult to use. Three studies examine how consumers balance their desires for capability and usability when they evaluate products and how these desires shift over time. Because consumers give more weight to capability and less weight to usability before use than after use, they tend to choose overly complex products that do not maximize their satisfaction when they use them, resulting in ”feature fatigue.” An analytical model based on these results provides additional insights into the feature fatigue effect. This model shows that choosing the number of features that maximizes initial choice results in the inclusion of too many features, potentially decreasing customer lifetime value. As the emphasis on future sales increases, the optimal number of features decreases. The results suggest that firms should consider having a larger number of more specialized products, each with a limited number of features, rather than loading all possible features into one product.